Study on Blockchain Visualization - Tri Sundara; Ideva Gaputra; Siska Aulia (Politeknik Negeri Padang, 2017)
Blockchain as a distributed ledger system which provide underlying technology behind Bitcoin. Blockchain paradigm can be extended to provide a generalized framework for implementing decentralized compute resources. Some attempts has been made to visualize Blockchain transaction flow. This research aims to assess those attempts through systematic review.